The quality of the functional work environment and its relationship to morale among a sample of administrative employees at the University of Damascus (Journal of Hama University, 2024)
The objective of the study was to identify the quality of the functional working environment and its relationship with the morale of a sample of administrative staff at the faculties and directorates of Damascus University. 50 staff members distributed by sex to 22 and 28 female staff members s work environment, where the four-pronged scale is the focus of promotion, job incentives, relationship with managers, colleagues, job safety and leadership behaviour, Also building a morale scale, the findings concluded that the overall assessment of the trend towards the quality of the functional working environment from the point of view of a number of staff at Damascus University colleges and directorates for promotion axis, job incentives, relationship axis with managers and colleagues, career safety axes and leadership behaviour axis was (average), as well as the overall assessment of the trend towards a morale scale from the point of view of a number of staff at Damascus University colleges and directorates in relation to the morale scale, was (median) Also, the findings also concluded that there were no statistically significant differences between the average grades of administrative staff at Damascus University on the measurement of the quality of the functional working environment and the measurement of morale according to the gender variable, and there were no statistically significant differences between the average grades of administrative staff at Damascus University on the measurement of the quality of the functional working environment and the measurement of morale scaledepending on the variable years of experience.and there is Correlation Statistically statistically significant between the average grades ofquality of the functional working environmentand the measurement of morale scale.The research put forward anumber of recommendations , the most important of which are the creation of asuitable social , psychological and physical climate for work and the need to establish centers for the development of human potential , which adopt special training programs to raise morale .